Effect Of The Extraction Methods On The Identification Of Caffeine In The Extract Of Dragon Fruit Peel - Reza pratama saputra; Nurlita Julianti; Azhari Firmansyah; Rhamal Amir; Aden Dhana Rizkita; Sintia Ayu Dewi (Indonesian Journal of Chemical Science, 2023)
Dragon fruit is a fruit that is abundantly available in Indonesia. Dragon fruit peel of Hylocereus sp. has become an increasingly popular natural ingredient in the food and beverage industry as it contains rich nutrients that can improve heart health, maintain healthy skin, support weight loss, boost our immune system, and make the body refreshed, including bioactive compounds such as alkaloids. The aim of this study was to identify the most effective extraction method in isolating caffeine compounds from dragon fruit peels. The methods used were maceration, percolation, reflux and fractionation extraction methods. Then for analysis using chromatography method KLT plate Silica Gel GF 254 and compound analysis using HPLC with flow rate of 2 ml/min, pump pressure 75 kgf/cm2, oven temperature 45o C, maximum temperature 85o C, wavelength 275 nm and isocratic eluent flow mode. Based on the research that has been done, it can be concluded that to determine the content of compounds in dragon fruit peel can be done by maceration, percolation and reflux methods. There is caffein at a retention time of 0.7 minutes